2017
DOI: 10.1007/s12602-017-9274-x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Inhibitory and Anti-oxidative Effects of Lactic Acid Bacteria Isolated from Dairy Cow Feces

Abstract: Overproduction and accumulation of melanin cause a number of skin diseases. The inhibitors of tyrosinase are important for the treatment of skin diseases associated with hyper-pigmentation after UV exposure and application in cosmetics for whitening and depigmentation. Reactive oxygen species (ROS) including hydrogen peroxide are generated by chemical substances and metabolic intermediates and cause various diseases including cancer and heart diseases. We have isolated four different lactic acid bacteria (LAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Pp2-459 176 and a toxic strain of the cyanobacterium, Oscillatoria agardhii 177 . Interestingly, some probiotics such as Lactobacillus sp 178 . which are used in the fermentation process have been investigated as natural tyrosinase inhibitor sources.…”
Section: Natural Tyrosinase Inhibitor Sourcesmentioning
confidence: 99%
“…Pp2-459 176 and a toxic strain of the cyanobacterium, Oscillatoria agardhii 177 . Interestingly, some probiotics such as Lactobacillus sp 178 . which are used in the fermentation process have been investigated as natural tyrosinase inhibitor sources.…”
Section: Natural Tyrosinase Inhibitor Sourcesmentioning
confidence: 99%
“…The mechanisms of action of packaging systems can be explained by enzymatic, (such as tyrosinase and polyphenol oxidase ac- A smaller class of alkaloids and polyphenols found in fungi, including Aspergillus sp., Paecilomyces sp., Trichoderma sp., Phellinus linteus, Daedalea dickinsii, and Dictyophora indusiata, have been reported to selectively block the enzyme and are a source of novel tyrosinase inhibitors [40,41]. Studies have shown that four distinct strains of lactic acid bacteria isolated from cow faeces exhibit tyrosinase inhibitory activity [80]. For instance, the most active compounds within the group of natural flavones, flavanols, isoflavones, and flavanones inhibited mushroom tyrosinase with an IC 50 of 44-500 µM, while natural anthocyanidins, aurones, and chalcones had an IC 50 ranging from 18 to 106.7 µM, which was in comparison to kojic acid (a potent inhibitor of tyrosinase) with a tyrosinase inhibitory activity of IC 50 of 59-318 µM (Table 3).…”
Section: Edible Coatings Essential Oils and Tyrosinase Inhibitorsmentioning
confidence: 99%
“…Melanin is the final product produced by melanogenesis and is influenced by various factors such as hormonal changes and nutritional status. Besides, melanogenesis can cause damage to cell membranes and DNA by generating free radicals, causing DNA lipid peroxidation, reducing membrane fluidity, and DNA mutations leading to cancer and degenerative diseases [4,5]. This melanogenesis occurs in melanocytes located in the epidermis basement layer, and tyrosinase acts as the main enzyme in this process.…”
Section: Introductionmentioning
confidence: 99%